192k views
3 votes
The zeros to the equation 3 x 2 − 5 x − 2 = 0 are x = 3 and x = 2.

Group of answer choices

True

False

1 Answer

3 votes

Answer:

False

Explanation:

Solving the equation

3x² - 5x - 2 = 0

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 3 × - 2 = - 6 and sum = - 5

The factors are - 6 and + 1

Use these factors to split the x- term

3x² - 6x + x - 2 = 0 ( factor the first/second and third/fourth terms )

3x(x - 2) + 1(x - 2) = 0 ← factor out (x - 2) from each term

(x - 2)(3x + 1) = 0

Equate each factor to zero and solve for x

x - 2 = 0 ⇒ x = 2

3x + 1 = 0 ⇒ 3x = - 1 ⇒ x = -
(1)/(3)

Solutions are x = 2 and x = -
(1)/(3)

User Warriorpostman
by
5.1k points